KINERJA KEPEMIMPINAN PEREMPUAN DALAM MENINGKATKAN DAYA SAING LEMBAGA PENDIDIKAN DI SMK AL-MUJTAMA’ PLAKPAK PEGANTENAN-PAMEKASAN - Wardhatul Khomairah; Siswanto Siswanto (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2019)
The Al-Quran is used as a guide for human in all aspects of life. In addition, the Koran also has conferred a status between men and women in the sense of normative and social status. However, the Koran also recognizes against superiority between men and women in certain contexts. If examined carefully, when women plunge into the public sphere, absolutely no hint in the Al-Quran that explains the opposition of a woman to become a leader including in becoming a leader of an educational institution. This study used a qualitative approach with a type of phenomenological research. Sources of data are obtained through interviews, observation and documentation. The informants are principals, teachers and students. Meanwhile, checking the validity of data is conducted through extention of participation, triangulation and negative case analysis method.